Análise dinâmica de conversores CC-CC boost-flyback de elevado ganho - Pontes, Jhonatan de Abreu Soares (2018)
This study has the purpose of modeling the dynamic behavior of the conventional and soft-switching boost-flyback DC-DC converters. This analysis is justified by the need of controlling key system variables, such as voltage and current, in applications requiring a high step-up ratio, as for example in renewable energy processing. The results are validated using a simulation software and from the testing of two prototypes with a nominal 500 W output power , 48 V input voltage, 400 V output voltage and switching 100 kHz frequency. The closed-loop operation is also verified using a PI compensator plus a low pass filter, aiming to keep the output voltage regulated at 400 V.